Antimitochondrial antibodies and antibodies to extractable nuclear antigens in patients with primary biliary cirrhosis - Oliva Menacho, José Enrique (2020)
Objective: To determine the frequency of antimitochondrial antibodies and antibodies to extractable nuclear antigens in patients with primary biliary cirrhosis. Methods: Cross-sectional study carried-out in the Servicio de Inmunología del Hospital Nacional Arzobispo Loayza from January 2018 to March 2019. Clinical charts of 30 patients with presumptive clinical features of primary biliary cirrhosis were reviewed. We used an immunologic blood kit and an immunofluorescence microscopy at 40K to detect antinuclear antibodies and antimitochondrial antibodies, an immunoblot was used to detect antibodies to extractable nuclear antigens. Results: 30 patients were included in the study, 20 were female (66.7%). The most frequent stain pattern was the cytoplasmic reticular mottled pattern; 17 (56.7%) followed by the mottled pattern, 7 (23.3%) and the least frequent pattern was the centromeric pattern. Nine patients (42.9%) with primary biliary cirrhosis had anti-M2. Most of the patients with primary biliary cirrhosis had antimitochondrial antibodies 21(70%). Conclusions: We found a high frequency of the cytoplasmic reticular mottled pattern among patients with primary biliary cirrhosis and an association with anti-M2 and with antimitochondrial antibodies.